Meaning in the history of English: words and texts in context ; [the 17th meeting of the International Conference on English Historical Linguistics (ICEHL) took place in Zurich in the last week of August 2012] - Jucker, Andreas H.; Landert, Daniela; Seiler, Annina; Studer-Joho, Nicole (Studies in language companion series, 2013)
This article explores the use of evidentials, or markers of source of information in witness depositions from England in the period 1680-1710. By comparing the results with those from a previous study on the Salem witch trials (Grund 2012), I point to significant similarities in the linguistic forms and deployment of markers signaling sensory evidence, inference, assumption, and quotatives (i.e. information based on what other people have said). I also demonstrate the importance of considering the socio-historical and situational context in the interpretation of the evidentials: the legal sett